2021
DOI: 10.1007/s00253-021-11539-w
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive plant secondary metabolites through in vitro technologies—status and outlook

Abstract: Medicinal plants have been used by mankind since ancient times, and many bioactive plant secondary metabolites are applied nowadays both directly as drugs, and as raw materials for semi-synthetic modifications. However, the structural complexity often thwarts cost-efficient chemical synthesis, and the usually low content in the native plant necessitates the processing of large amounts of field-cultivated raw material. The biotechnological manufacturing of such compounds offers a number of advantages like predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 176 publications
1
36
0
Order By: Relevance
“…Our results indicated that the degree of callus growth from H. tuberculatum immature seeds is moderate profuse to profuse with 2,4-D, while there was only a light callus growth resulting with BAP. This is in agreement with previous research, where optimal callus induction on MS medium was achieved with 2 mg/l 2,4-D ( Wawrosch and Zotchev, 2021 ). Although a high concentration of 2,4-D resulted in profuse callus growth, a high concentration of 2,4-D can decrease regeneration frequency, and calluses tend to remain in the callus proliferation stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicated that the degree of callus growth from H. tuberculatum immature seeds is moderate profuse to profuse with 2,4-D, while there was only a light callus growth resulting with BAP. This is in agreement with previous research, where optimal callus induction on MS medium was achieved with 2 mg/l 2,4-D ( Wawrosch and Zotchev, 2021 ). Although a high concentration of 2,4-D resulted in profuse callus growth, a high concentration of 2,4-D can decrease regeneration frequency, and calluses tend to remain in the callus proliferation stage.…”
Section: Discussionsupporting
confidence: 93%
“…Extracts have also demonstrated antifungal and antiviral properties against Fusarium culmorum, Rhizoctonia solani , and tobacco mosaic virus (TMV), having a high concentration in resveratrol kaempferol, myricetin, rutin, quercetin, and rosmarinic acid ( Chandran et al, 2020 ). Thus organ cultures or cell cultures will be a potential source to produce and extract bioactive compounds on an industrial scale ( Chandran et al, 2020 ; Wawrosch and Zotchev, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enormous plants, mainly medicinal plants, that can produce bioactive secondary metabolites include Chinese medicinal herbs, as reported by El-Ramady et al [86] and in Tables 2 and 3. The production of bioactive plant secondary metabolites is common using in vitro technologies [87,88]. All plant species can form primary metabolites in cells, but secondary metabolites vary by plant species and can be produced through metabolic pathways derived from the primary metabolic pathways.…”
Section: Medicinal Plants and Their Bioactive Compoundsmentioning
confidence: 99%
“…Enormous plants, mainly medicinal plants, that can produce bioactive secondary metabolites include Chinese medicinal herbs, as reported by El-Ramady et al [86] and in Tables 2 and 3. The production of bioactive plant secondary metabolites is common using in vitro technologies [87,88]. On the other hand, nutraceuticals have great potential for human health.…”
Section: Medicinal Plants and Their Bioactive Compoundsmentioning
confidence: 99%
“…The production of a wide array of secondary metabolites have been explored in hairy roots. These include compounds such as alkaloids, anthocyanins (Barba-Espín et al, 2020), flavonoids, ginsenosides, phenolics, stilbenes, lignans, and terpenoids (Wawrosch and Zotchev, 2021). Hairy roots have also been used for the production of protein based products such as vaccines (Skarjinskaia et al, 2013;Massa et al, 2019), monoclonal antibodies (Donini and Marusic, 2019), and therapeutic proteins (Cardon et al, 2019;Zhang et al, 2019b).…”
Section: Introduction: Why Hairy Roots?mentioning
confidence: 99%